Evaluasi Pemanfaatan Aplikasi GDL (Ganesha Digital Library) Sebagai Aplikasi Repositori di Politeknik Negeri Bandung - Arvelina, Erlin; Tresnawaty, Yani; Gemalia, Idayu (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
The GDL repository system application has been used by the Politeknik Negeri Bandung (Polban) since 2005 until now and never been done its evaluation. Ideally the application is evaluated and analyzed its system, utilization level and information organization of its features and menus. The purpose of research is to evaluate and discover advantages and disadvantages of Polban Institution Repository Application from the system components and uses, to discover parts of the system required further development to support the dissemination of repository information. This research uses descriptive qualitative method. Data were collected from observations of the existing repository system and indirect interviews with users. The data were analyzed by triangulation method that compared observation data with the results of interviews. References studies are also concluded to strengthen data analysis. The evaluation reveals the advantages of the repository system, including metadata descriptions still appropriate for users and data exchange using the OAIPMH protocol. As for disadvantages, usage statistics are unavailable. Utilization data of Digilib Polban obtained using Google Analytics. In addition, supporting hardware and software in application operations (for servers) are far behind so that it can affect the accessibility and security of uploaded data.